Royal and urban gunpowder weapons in late medieval England - Spencer, Dan (Armour and weapons ;, 2019)
One of the most important technological developments of the Middle Ages was the adoption of gunpowder weapons in medieval Europe. From the fourteenth century onwards, this new technology was to eventually transform the conduct of warfare beyond all recognition with important implications for European and global history. Guns came to be used in all aspects of military operations, with kings, nobles and burgesses all spending large sums of money on these prestigious weapons. The growing effectiveness of gunpowder artillery prompted major changes in the design of fortifications, the composition of armies, the management of logistics and administrative systems.0 This book is the first full-length study of the unique English experience of gunpowder weapons, tracing their development from their introduction in the reign of Edward III to the end of the fifteenth century. The rich records of the English Exchequer and urban accounts are used to explore their role in campaigns, in sieges, on the battlefield, at sea and their role in the defence of towns, royal castles and the fortifications of the Pale of Calais. It provides a comprehensive framework for the speed of technological advances and the factors responsible for these changes, as well as an in-depth discussion of individual gun types.